Inhibition by human T-lymphotropic virus (HTLV-I) of T-lymphocyte mitogenesis: failure of exogenous T-cell growth factor to restore responsiveness to lectin. - Wainberg, M A (1985)
Various retroviruses, including human T-cell lymphotropic virus (HTLV-I) and avian sarcoma virus (ASV), can prevent coincubated human peripheral lymphocytes from responding efficiently to phytohaemagglutinin. Addition of high concentrations of T-cell growth factor (TCGF) activity usually overcomes this inhibition. However, such restoration of responsiveness does not occur in the case of HTLV-coincubated cells.